Analisis Pragmatis Hiperbola dalam Lirik Lagu: Studi Perbandingan antara “I Wanna Be Yours” oleh Arctic Monkeys dan “Annabel Lee” oleh Stevie Nicks sebagai Adaptasi Puisi: Analisis Pragmatis Hiperbola dalam Lirik Lagu: Studi Perbandingan antara “I Wanna Be Yours” oleh Arctic Monkeys dan “Annabel Lee” oleh Stevie Nicks sebagai Adaptasi Puisi - Putri Pujiyawati; Siti Nopita; Tatu Siti Rohbiah (Universitas Swadaya Gunung Jati, 2026)
This study investigates the use of hyperbole in song lyrics through a pragmatic lens, focusing on a comparative analysis of “I Wanna Be Yours” by Arctic Monkeys and “Annabel Lee” by Stevie Nicks, both of which are adaptations of classic poems. Employing a qualitative descriptive method, the research analyzes the lyrics to identify hyperbolic expressions and interpret their pragmatic functions. Data were collected through documentation and close reading of the song lyrics, followed by systematic coding and categorization of hyperbolic instances. The analysis reveals that both songs utilize hyperbole to intensify emotional expression, create vivid imagery, and emphasize key themes such as love, devotion, and longing. “I Wanna Be Yours” is found to contain a greater variety and frequency of hyperbolic expressions, often highlighting the speaker’s desire for closeness and unwavering support. In contrast, “Annabel Lee” employs hyperbole to elevate the depth and tragedy of love, aligning with the melancholic tone of Poe’s original poem. The findings demonstrate that hyperbole in song lyrics serves not only as a stylistic device but also as a communicative tool that shapes listener perception and emotional engagement. This comparative pragmatic analysis contributes to a deeper understanding of how exaggerated language operates in artistic adaptation, bridging poetry and music to enrich the audience’s interpretive experience.